César Franck: selected piano compositions - Franck, César. 1822-1890 (Dover collections for the piano, 1992)
Through his teaching and through his innovative instrumental works, César Franck (1822-1890) was one of the most influential French composers of the 19th century. This outstanding edition of selected works for piano has been edited by Franck´s famous pupil and biographer, Vincent d´Indy. It includes ten pieces, evenly divided between early germinal compositions and important late pieces.